Optimalisasi Psikologi Pendidikan dalam Pengembangan Potensi Anak Berkebutuhan Khusus di SLBN Banjarnegara - Ishaq Abdul Hannan; Qurotu Aini; Khusnul Khotimah; Anisa Nur Fatah; Salma Khusna Wahda; Neli Maghfiroh; Shabrina Eka Witrie; Hidayatun Munawaroh (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The application of educational psychology at SLBN Banjarnegara is an important step to support the development of children with special needs (ABK). The aim of this study is to analyze the effectiveness of the application of educational psychology in improving the quality of learning and development of ABK, as well as identifying the obstacles faced and strategies for overcoming them. The research method used is a qualitative approach with a descriptive design, collecting data through in-depth interviews, observation and documentation. The results of the analysis show that the application of educational psychology significantly contributes to students' cognitive, social and emotional development. Implemented interventions, such as play therapy and positive reinforcement, have proven effective in increasing student motivation and engagement. However, this research also identified a number of obstacles, such as a lack of competent teaching staff and limited adequate facilities. Efforts to overcome these obstacles, including training for teachers and development of educational facilities, are discussed in detail. It is hoped that this research can provide deeper insight into the application of educational psychology at SLB N Banjarnegara, as well as provide recommendations for the development of better inclusive education for children with special needs in the future.